Willingness to participate in Payment for Mangrove Environmental Services: Maritime sector and shipping industry stakeholder perspectives - Pham Thu Thuy; Đặng, L.H.; Tăng Thị, K.H.; Đặng, H.P.; Hoàng, T.L.; Phạm, T. Thuyền; Nguyễn Thị, K.N.; Nguyen Thi, V.A.; Nguyen Thi, T.A.; Phạm, T. Tuấn (Center for International Forestry Research, 2021)
The Government of Vietnam has recently introduced many new policies promoting economic development and environmental protection through sustainable development of the shipping industry, including the Green Port Program and a Payment for mangrove environmental services mechanism.